The Adoption Rate of Reagent Masofilm Innovation as Teat Dipping to Prevent Mastitis in Kemiri Village, Jabung District, Malang Regency - Anie Eka Kusumastuti; Suprih Bambang Siswijono; Nailul Faizah (Kadiri University - Faculty of Agriculture, 2023)
The research purpose was to identify the dairy farmer's characteristics and analyze the innovation in the adoption of innovative technologies, which as reagent masofilm teat dipping to dairy cattle in Kemiri Village, Jabung District, Malang Regency. Data was obtained by observation participation and direct interview with 39 dairy farmers from KAN Jabung active members from February - March 2020. This research uses primary and secondary data, with participation observation, direct interviews with respondents with a Likert scale (score 1-3), and documentation as a data collection method. Data was then analyzed by using simple statistics and descriptive analysis. The results showed that the majority of dairy farmers in Kemiri Village are productive ages ranging from 25-38 years old, graduated from elementary school, have experience keeping livestock for around 21 years with several livestock ownership around 11-15 head/farmers and using 2 devices to find the information regarding the reagentmasofilm as teat dipping. In addition, the adoption rate of dairy farmers in Kemiri Village, Jabung District, Malang Regency was 76.92% in the fast category, 15.39% in the medium category and 7.69% in the slow category.